Democracia em tempos sombrios: desafio da educação e das políticas educacionais na formação democrática - Mezadri, Neri José (2022)
The thesis "Democracy in dark times: challenges of education and educational policies in democratic formation", defended at PPGEDU/UPF, in the line of Educational Policies, aimed at understanding the crisis of democracy in contemporary times, as well as thinking about formative processes and educational policies perspectives that lead to autonomy and social emancipation, aiming at a high-intensity democracy. The problem investigated concerns how to strengthen and broaden radical democratic experiences, considering the context marked by competitive rationality, subjective impoverishment, and the crisis of representativity that affects, above all, politics. The hypothesis points to the need for structural transformation, based on political pressure on governmental measures (the State), and of mentality, in the direction of the principle of cooperation. The methodology privileged bibliographical research, as well as documental sources and statistical data. A wide selection of authors was developed in order to build a comprehensive diagnosis of the reality and to prospect a new "social grammar" based on historical experiences. The trajectory followed to account for this undertaking was structured in three theoretical chapters: "Tension between (neoliberal) capitalism and democracy"; "Ambiguities and potentialities of democracy inaugurated in the 21st century"; "Conditions for education for democracy". We affiliate ourselves, in this task, to the dialectic tradition to account for the complexity of events, aiming to overcome linear interpretations of the facts that involve the field of education. This exercise sought to perform a social hermeneutics, identifying the reaches and limits of democracy in order to project democratic advances conceived as a way of life and not only as a regime for choosing representatives. The research revealed that the task of educating for democracy is complex and that this requires an articulated movement between individual subjects and social groups, mediated by formative processes sustained by a notion of collective belonging. It is not, therefore, a task restricted to formal education, but should privilege a broad cultural formation for society as a whole, through the challenge of constituting and articulating themselves in "communities" with common projects. It was found that, in the current context, it is essential to problematize the functioning of neoliberal capitalism in its various forms of power capture by large corporations and the emptying of the content of democracy that occurs through the kidnapping of subjectivity and the predominance of a competitive rationality. The conclusion points to the challenge of consolidating quality public education and the improvement of democratic networks through the action of groups sustained by critical-reflexive thinking and guided by the utopia of cooperation and reciprocity. Educating for democracy implies, therefore, sustaining a democratic conception as a dynamic of permanent amplification of spaces of direct participation of citizens and a notion of education as a social process of exchange of knowledge constituting social behaviors.